2013
DOI: 10.1093/mp/sst080
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integrated Method for Large-Scale Detection, Identification, and Quantification of Widely Targeted Metabolites: Application in the Study of Rice Metabolomics

Abstract: Liquid chromatography-mass spectrometry (LC-MS)-based metabolomics has been facilitated by the construction of MS(2) spectral tag (MS2T) library from the total scan ESI MS/MS data, and the development of widely targeted metabolomics method using MS/MS data gathered from authentic standards. In this report, a novel strategy called stepwise multiple ion monitoring-enhanced product ions (stepwise MIM-EPI) was developed to construct the MS2T library, in which stepwise MIM was used as survey scans to trigger the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
1,058
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,268 publications
(1,063 citation statements)
references
References 54 publications
(29 reference statements)
4
1,058
0
1
Order By: Relevance
“…It has been reported that the Indica rice variety exhibits higher C-glycosylflavonoid production than the Japonica variety. 19,24,25,29) Principal component analysis (PCA) using the metabolome data characterized the accumulation patterns of the metabolites in the samples and showed the organ specificity of the metabolites (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the Indica rice variety exhibits higher C-glycosylflavonoid production than the Japonica variety. 19,24,25,29) Principal component analysis (PCA) using the metabolome data characterized the accumulation patterns of the metabolites in the samples and showed the organ specificity of the metabolites (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20] Such metabolites exhibit properties beneficial to humans, including anti-tumor, 21) anti-inflammatory, 22) and anti-oxidant activities. 8) To improve the quality of rice plants, the organ-specific metabolic networks of primary and specialized metabolites were recently investigated using metabolite profiling based on liquid chromatography (LC)-MS.…”
Section: Abstract Oryza Sativa; Rice; Specialized Metabolite; Anti-imentioning
confidence: 99%
See 1 more Smart Citation
“…described previously (12,14) (Dataset S1). A data matrix was generated, consisting a total of 1,000 metabolites including 683 in flag leaf and 317 germinating seed, with 100 metabolites were detected in both tissues ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Here, we report a genetic analysis of rice metabolome combining metabolic profiling (12) with an ultrahigh-density genetic map (13) using a recombinant inbred line (RIL) population. We demonstrated that the high-resolution mapping of the large number of mQTLs may greatly accelerate gene identification and pathway elucidation for metabolites, which will enhance our understanding of the genetic and biochemical basis of the metabolome and also be valuable for crop genetic improvement through metabolomics-assisted breeding.…”
mentioning
confidence: 99%